(untitled) (KIUT Publication, 2025)
The shrinking of the Aral Sea and the resulting ecological disaster have had a negative impact on the environment, economy, and social life of Central Asia. This article analyzes innovative strategies applied in the protection and restoration of the Aral Sea and evaluates their ecological and economic effectiveness. Based on water resource management, bio-conservation technologies, and international cooperation projects, comprehensive solutions are developed to restore nature and improve the well-being of the local population. The research results highlight the importance of innovative approaches aimed at ensuring the region’s ecological sustainability and increasing its economic potential.